1997
DOI: 10.1063/1.118701
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of boron nitride thin-film reflectivity spectra by generalized ellipsometry

Abstract: Articles you may be interested inCharacterization of cubic boron nitride growth using UV-extended real-time spectroscopic ellipsometry: Effect of plasma additions and dynamic substrate bias steps Cubic boron nitride thin film deposition by unbalanced magnetron sputtering and dc pulsed substrate biasing Phase and microstructure investigations of boron nitride thin films by spectroscopic ellipsometry in the visible and infrared spectral range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 15 publications
4
59
0
Order By: Relevance
“…12 Such samples have already been studied by gVASE in the VIS spectral range, resulting in VIS optical constants. 7 It was found that the h-BN thin films possess an effective optical axis perpendicular to the sample surface. The microscopic c axes of the h-BN grains are more or less tilted by the same inclination angle ⌰ from the sample normal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Such samples have already been studied by gVASE in the VIS spectral range, resulting in VIS optical constants. 7 It was found that the h-BN thin films possess an effective optical axis perpendicular to the sample surface. The microscopic c axes of the h-BN grains are more or less tilted by the same inclination angle ⌰ from the sample normal.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the growth conditions, the h-BN layer grain c axes show an average preferential orientation with respect to the film normal. 7 This average orientation varies as a function of the growth condition (U B ) as well. Some of the h-BN layers contain isotropic material with randomly oriented grain c axes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ex situ ellipsometry was recently used to determine the isotropic c-BN ͑e.g., at ϭ571 nm: n c ϭ2.1͒, and anisotropic h-BN ͑n e ϭ1.65, n o ϭ2.1͒ optical constants and thin-film layer structure of magnetron sputtered BN. [19][20][21] . It was observed that the h-BN and c-BN thin-film optical constants are very similar to their bulk values.…”
Section: ͑1͒mentioning
confidence: 99%